Sunda-“Java” and The Past : A Socio-Historical Reflection - Fachry Ali (Insaniyat : Journal of Islam and Humanities, 2016)
This piece directs its attention to the psycho-historical consciousness between two major Indonesia’s ethnic  groups:  Sunda  and  Java.  The  14th  century  of  Bubat  War  in  Majapahit,  East  Java  and  the Central Java Mataram Kingdom’s “occupation” over the Land of Sunda in 16th and 17th centuries had created psychological problem that marked an uneasy relations between both of these ethnic groups,  when  the  nationalism  fountainhead  is  refered  to  the  heyday  histories  of  the  East  and Central  Java’s  kingdoms.  The  Sundanese  nationalism  finally  was  flown  into  modern  Indonesian nationalism.  By  choosing  the  latest,  the  Sundanese  were  freed  from  the  past  bitter  memories.DOI: 10.15408/insaniyat.v1i1.4350